Criminal Liability of Medical Profecionals Negligience: Comparative Analysis - Danchenko, Kateryna; Taran, Olga (Cuestiones Políticas, 2020)
The purpose of this article is to study the criminal liability of medical professionals in cases of suspension, in accordance with jurisprudence in Ukraine, the European Union and the United States of America (USA). He made the comparative method. According to the investigation, the number of criminal proceedings in Ukraine by the authority and misconduct of medical doctors is about 2% per population, my figure that rises to 30% in Europe and is the stable yes in the US and is 28%. 32%. The main objective of the article is often area identify specializations in the medical office occurs with the mayor based on Ukrainian jurisprudence (data from Ukraine’s only state judicial decision register from 2016 to 2019). In addition, the study analyses the impact of the main influences on the ability of medical professionals for their professional functions. From counting the results show that surgeons, gynecologists, paramedics, and anesthesiologists are the most prone to deviation and medical error. Key proposed criteria have been proposed as medical errors differ from medical writing.